Public support models of agricultural production in the EAEU countries - Taipov, Т.А. (BUKETOV BUSINESS REVIEW, 2018)
The role of agro-food market development and ensuring food security in the national security system has been considered. Main factors contributing to the implementation of the State policy have been presented. Specifics of competitive agribusiness have been revealed using the example of the United States. Priority directions of economic mechanism improvement in the EAEU countries, as well as basic principles of the development and implementation of a unified agricultural and food policy in the areas of the Eurasian agro-food market, agro-industrial production, State regulation of AIC, conditions of implementation of agricultural enterprise financial rehabilitation mechanism have been considered. The authors state that introduction of a comprehensive approach to public support for agricultural sector of economy will provide equal conditions for agricultural producers in the EAEC member countries. The model of public support in the Commonwealth countries, a model of public support for agricultural production in Kazakhstan for 2017-2021 have been proposed. The directions of subsidizing crop production, processing crop production and livestock products in the republic have been analyzed. The implementation of the investment subsidy program is aimed at cost reduction of investment and reduction of payback period of investment projects. Measures supporting the effective functioning of economic mechanism in the sphere of taxation, pricing, lending, and insurance have been justified. The conclusion is made that unification of public administration mechanism in the EAEU countries will create equal economic conditions for agricultural producers, increase production efficiency, solve problem of providing population with food, and other important issues of agricultural science.